United States and Mexico Ties That Bind, Issues That Divide - Aguila, Emma (RAND Corporation, 2012)
This binational reference for U.S. and Mexican policymakers presents the interrelated issues of Mexican immigration to the United States and Mexico's economic and social development. Differences in economic growth, wages, and the employment situation between two countries are critical determinants of immigration, and migration of labor out of Mexico, in addition to economic and social policies, affects Mexico's development.